Efficacy of topical vancomycin application in cardiac surgery to reduce deep sternal wound infection: a randomised control trial at tertiary cardiac care hospital - Shah, Soham J.; Jadhav, Uday E. (International Surgery Journal, 2022)
Background: Mediastinitis is lethal complication and a challenge in post cardiac surgery patients. We aim at evaluation of topical vancomycin by applying it at sternal edge in prevention of deep sternal wound infection. Methods: The vancomycin group had local application of vancomycin paste prepared by mixing 1gm of powder in 3 ml of normal saline and stirred until paste was formed. The control group had reinforced closure technique without vancomycin paste application. All cases were followed up for symptoms and signs of sternal wound infection during hospital stay and uptil 1 month. Results: There was increase incidence of wound infection with control group as compared to vancomycin group, there were no wound infection in patients of vancomycin group. Conclusions: Application of topical vancomycin significantly reduces post-sternotomy wound infection and prevents deep mediastinitis.